2017
DOI: 10.1016/j.ast.2016.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamics and flight mechanics of MAV based on Coandă effect

Abstract: With the progress and development of Coandă Micro Air Vehicle (MAV) to date, various configurations have been proposed and developed. For the purpose of designing a Micro Air Vehicle (MAV), that could meet the desired mission and design requirements and can operate effectively in various environmental conditions, a workable theoretical analysis is to be developed. With such motivation, capitalizing on the basic fundamental principles, the aerodynamic forces acting on Coandă MAV configurations are revisited and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…al. [13] and Schroijen and van Tooren [8] for two-dimensional cylindrical Coandă design model. From Figure 4, the result (solid line) have shown a good correlation and in agreement with the CFD data [3].…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…al. [13] and Schroijen and van Tooren [8] for two-dimensional cylindrical Coandă design model. From Figure 4, the result (solid line) have shown a good correlation and in agreement with the CFD data [3].…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Basics of circulation control aerodynamics [3] Two versions of analytical formulation using control volume approach for the cylindrical Coandă aircraft have been presented by Schroijen and Van Tooren [8] and Ahmed et al [13]. In the first version [8], it has been concluded that the lift force is dependent on the jet velocity, outflow angle, dimensions of the jet slot, and introducing an efficiency parameter to capture the viscous effect.…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations